FENOMENA INFLASI, PENGANGURAN DAN PERTUMBUHAN EKONOMI DI INDONESIA: PENDEKATAN KURVA PHILIPS DAN HUKUM OKUN - Sukanto Sukanto (Department of Development Economics, Universitas Sriwijaya, 2015)
The objective of this study was to show the correlation between inflation, unemployment, and economic growth in Indonesia. Time series data from 1984 to 2013 were used to carry out descriptive analysis and regression using the VAR model. Results from this study are in agreement with the Philips' finding which states that there is a trade-off between inflation and unemployment. Meanwhile, the relationship between economic growth and changes in unemployment as stated by Okun's Law occurs in Indonesia. This is reflected in the Scatter plot which shows that there is a negative relationship between the two variables. Furthermore, results of the VAR regression model indicate that both inflation and economic growth affect unemployment. The impulse response graph shows that the variables will be convergent towards the equilibrium point or return to the previous equilibrium. The response of unemployment as a result of inflation shock and economic growth over a period of 10 years was found to be convergent. Based on the FEVD output, it can be seen that an important source of variation in unemployment was the shock of unemployment itself while the shocks which are related to inflation and economic growth are relatively small. Keywords: Inflation, unemployment, economic growth, Autoreggresive variation